Decision Support System For Admission Of New Employees With Weighting Method (Weight Product Model) - Miki Wijana; Asep Wibowo; Larasati Larasati (International Journal of Ethno-Sciences and Education Research, 2023)
Firli Group is an e-commerce and digital marketing company. At every new employee recruitment, Firli Group is still manual or semi-computerized, making it difficult to determine prospective new employees. Therefore we need a system that can be petrified to facilitate decision making, namely by using the Weight Product Model (WPM). WPM is a model of Decision Support System (DSS), namely by ranking, this analysis is carried out with a sample of 5 people. Decision support system on the acceptance of new employees, is expected to help the company.